Demographic and Parental Factors Associated With Developmental Outcomes in Children With Intellectual Disabilities - Vilaseca, Rosa; Rivero, Magda; Bersabé, Rosa M.; Cantero, María-José; Navarro-Pardo, Esperanza; Valls-Vidal, Clara; Ferrer, Fina (Frontiers in Psychology, 2019)
The aim of the study was to examine the relation between demographic variables, parental characteristics, and cognitive, language and motor skills development in children with intellectual disabilities (ID). A sample of 89 children with ID, aged 20–47 months, completed the Bayley Scales of Infant Development to measure cognitive, motor, and linguistic development. Parents were administered questionnaires about demographic information and parental anxiety, depression, parental stress, conjugality and familial functioning. Parenting behaviors (affection, responsiveness, encouragement, and teaching) were observed using the Spanish version of PICCOLO (Parenting Interactions with Children: Checklist of Observations Linked to Outcomes). A bivariate analysis showed that cognitive development in infants was significantly related to the mother’s and father’s responsiveness, and to the father’s teaching scores. Infant language development was related to a variety of maternal factors (educational level, anxiety, depression, maternal responsiveness) and to the father’s teaching scores. None of the factors were statistically related to child motor development. A multivariate regression analysis indicated that children’s cognitive development can be predicted by a linear combination of maternal responsiveness and paternal teaching scores. Language development can be predicted by a linear combination of maternal anxiety and responsiveness, and paternal teaching scores. The present study provides evidence of the importance of paternal involvement for cognitive and language development in children with intellectual disabilities, and contributes to the increasing literature about fathering. Gaining knowledge about parental contributions to children’s development is relevant for improving positive parenting in early intervention programs.